Tick-Borne Encephalitis Virus Infection in a Two-Year-Old Child Returning from Switzerland (July–August 2023): Is It Time for TBE Immunization of Serbian Travelers? - Verica Simin; Ognjen Ležakov; Ivana Bogdan; Dragana Mijatović; Dragana Gazibara; Lidija Popović-Dragonjić; Gordana Vijatov Đurić; Borko Milanović; Jelena Kesić; Andrea Đuretić; Ágota Ábrahám; Zsófia Lanszki; et al. (Pathogens)
Tick-borne encephalitis (TBE) is a vaccine-preventable viral infection that poses significant public health challenges, particularly in regions where tick-borne diseases are endemic. This case report describes a 2-year-old boy with confirmed abortive TBEV infection following a tick bite during travel to Switzerland. The patient developed fever and mild symptoms but did not exhibit central nervous system involvement. The case underscores the importance of raising awareness among healthcare providers and travelers from non-endemic areas, such as Serbia, about TBE risk and the potential benefits of preventive vaccination. Strategic immunization campaigns could mitigate the public health impact of travel-related TBE.